Penguatan Spiritualitas Berbasis Hadis Sebagai Upaya Preventif Burnout Pada Mahasiswa Gen Z - Khildah Salsabilatun Najah; Nasrulloh (Al-Kindi, 2026)
Generation Z lives in a fast-paced digutal era, full of academic, social, and emotional demands, making them more vulnerable to burntout. Burntout among gen z students appears in the form of mental, emotional, and physical fatigue due to continuous pressure. On the other hand, islamic teachings through the sayings of Prophet Muhammad SAW offer spiritual values that can serve as a preventiive strategy for maintaining mental health. This study aims to analyze the role of spiritual values in hadith as an effort to prevent burnout among gen z students. The research uses a literature review method with a qualitative approach through the analysis of psychology literature, hadith books, scientific artivles, and several supproting interviews. The study results indicate that spiritual values such as patience, trust in God (tawakkal), moderation (wasathiyah), rememberance of God (dhikr), and self-purification (tazkiyah al-nafs) can strengthen emotional regulation and mental redilience in students. These values are also in line with the concepts of coping in modern psychology, both problem-focused coping and emotion-focused coping, thus helping students face academic and social pressures more balancedly. Furthermore, hadith-based spirituality provides a sense of meaning, inner peace, and clear life direction, which are importantt factors in preventing burnout. Therefore, this study concludes that spiritual values in the hadith have significant potential as a preventive approach to enhancing the mental well-being oh Gen Z students amidst the dynamics and challenges of the digital age.